Mental health symptom burden in elite ice hockey players and its association with self-reported concussive events - Mitchell J. Andersson; Göran Kenttä; Emma Claesdotter-Knutsson; Anders Håkansson (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Some studies suggest that elite athletes experience adverse mental health symptoms at rates commensurate with the general population, despite the well-established buffering effects of exercise. Within contact sports, such as ice-hockey, recurrent concussions may be a source of this discrepancy. We compared the point prevalence of various mental health outcomes with other athlete and general population samples, as well as investigated their relationship with concussive events. Methods We surveyed 648 active ice hockey players from the top two men’s tiers and the top women’s tier in Swedish elite ice hockey on lifetime concussive events, hazardous alcohol use, problematic social media use, depression, anxiety, and burnout. Results Hazardous alcohol use was more prevalent among male ice hockey players (29.5% AUDIT-C ≥ 6) compared to other athlete and general population samples, while other mental health symptoms were less common. Female ice hockey players reported higher hazardous alcohol consumption (36.4% AUDIT-C ≥ 4) than another athlete sample and more burnout (19.1%) than the general population. After adjusting for covariates, athletes with 3+ concussive events had 2.1 times the odds of elevated depressive symptoms and 3.5 times the odds of elevated burnout symptoms compared to those with no concussion history. Treating lifetime concussive events as a continuous predictor revealed positive correlations with all outcomes except for hazardous alcohol use. Conclusions Mental health outcome rates among active elite ice hockey athletes differ from those of other athlete and general population samples, whilst concussive events may be particularly linked to elevated symptoms of depression and burnout.